Nutritional Status of People with Schizophrenia in Sidoarjo District and its review according to Islamic View - Ade Ruslan; Citra Fitri Agustina (Junior Medical Journal, 2023)
Schizophrenia is a psychiatric illness that affects the brain and causes strange thoughts, perceptions, emotions, movements and behaviors. Schizophrenia is associated with many health problems that will increase morbidity and mortality due to changes in body weight. Lack of nutrition will make the body more susceptible to infection, while excess nutrition can trigger degenerative diseases. Decreased ability to care for oneself in schizophrenic patients can cause the patient's nutritional status to become malnourished or even malnourished. The purpose of this study was to determine the demographics and nutritional status of people with schizophrenia in Sidoarjo Regency. The method used in this research is descriptive quantitative method. The type of analysis used in this research is univariate data analysis. The results showed that people with schizophrenia in Sidoarjo district, especially in Wonoayu, Krian, and Tarik sub-districts, as many as 30 people (17.6%) were included in the Underweight category, 62 people (36.5%) were included in the Normal Weight category. 29 people (17.1%) were included in the overweight category with Risk, 38 people (22.4%) were included in the Obesity I category, 11 people (6.5%) were included in the obesity category II.